2008
DOI: 10.1021/bc800289a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Peptide Linkers for Highly Potent Antibody−Auristatin Conjugate

Abstract: Auristatins are highly potent antimitotic agents that have received considerable attention because of their activities when targeted to tumor cells in the form of antibody-drug conjugates (ADCs). Our lead agent, SGN-35, consists of the cAC10 antibody linked to the N-terminal amino acid of monomethylauristatin E (MMAE) via a valine-citrulline p-aminobenzylcarbamate (val-cit-PABC) linker that is cleaved by intracellular proteases such as cathepsin B. More recently, we developed an auristatin F (AF) derivative mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 17 publications
(34 reference statements)
0
108
0
Order By: Relevance
“…We chose to use auristatin, a highly potent tubulin inhibitor, because it is well characterized and can be modified for facile coupling to an antibody (10,30). Although the first generation of auristatin-linker conjugates were coupled to the N terminus of the peptide and contained a cathepsin B protease cleavage site, Doronina et al synthesized C-terminally linked derivatives that were reported to be more cytotoxic and have improved pharmacological profiles (30 (31), presumably because of degradation of the ADC in the lysosome and release of drug. Therefore, we first chose to investigate ADCs containing a noncleavable linker (nAF) coupled to the C terminus of auristatin F (AF) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to use auristatin, a highly potent tubulin inhibitor, because it is well characterized and can be modified for facile coupling to an antibody (10,30). Although the first generation of auristatin-linker conjugates were coupled to the N terminus of the peptide and contained a cathepsin B protease cleavage site, Doronina et al synthesized C-terminally linked derivatives that were reported to be more cytotoxic and have improved pharmacological profiles (30 (31), presumably because of degradation of the ADC in the lysosome and release of drug. Therefore, we first chose to investigate ADCs containing a noncleavable linker (nAF) coupled to the C terminus of auristatin F (AF) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AF was synthesized as previously reported (30). The noncleavable ethylene glycol linker derivatized with an alkoxy-amine was synthesized, as previously described (33), and attached to the C terminus of AF (SI Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several disulfide-linked ADCs are currently under clinical investigation (Table 1), more stable cleavable linkers are engineered in the form of lysosomal protease substrates, e.g. containing a valine-citrulline dipeptide bond, which is specifically cleaved by cathepsin B [26][27][28] .…”
Section: Linker Chemistriesmentioning
confidence: 99%
“…[10][11][12][13][14] Appropriate linker technology will ensure the general stability of ADCs during in vivo circulation and efficient drug release once internalized. 4,10,15 Linkers are generally categorized into 2 groups: cleavable and non-cleavable.…”
Section: Introductionmentioning
confidence: 99%